Reliability of functional fitness tests in women from 60 to 80 years - Jair Sindra Virtuoso Júnior; Ricardo Oliveira Guerra (Desafio Singular, 2011)
The aim of the present study was to verify the reliability expressed by the internal consistency and stability of two series of specific functional fitness tests (AAHPERD and Fullerton) in elderly populations. Thirty-six women, mean age 68-year-old, were selected (SD = 6.64). Parameters of functional fitness evaluated were: body strength, flexibility, agility and dynamic balance, coordination, and aerobic endurance. Descriptive statistics were used to analyze the data and describe the sample (frequency, mean and standard deviation), and the intraclass correlation coefficient (ricc) was used to verify the concordance between the stability and internal consistency of the tests. Estimated intervals of 95% of reliability was adopted. In general, the two series showed acceptable rates of reliability, the ricc varying from 0.60 to 0.94. Fullerton test proved to be more consistent in the ricc of the proposed tests, mainly in relation to flexibility of the hip and the two-minute-stationary-walking test for the evaluation of aerobic endurance. Results allowed for the conclusion that both series of tests present acceptable levels of reliability.